EVALUASI PROGRAM PENDIDIKAN SISTEM GANDA BERDASARKAN STAKE COUNTENANCE MODEL (Innovative Journal of Curriculum and Educational Technology, 2012)
Tujuan  Penelitian  ini  adalah  mengetahui  tingkat  keterlaksanaan Program  Pendidikan  Sistem  Ganda (PSG) pada tahapan 1) masukan (antecedents), 2) proses (transactions), 3) hasil (output). Subyek Penelitian meliputi Wakil Kepala  Sekolah  bidang  kurikulum, Wakil Kepala  Sekolah  bidang Humas DuDi, Wakil Kepala Sekolah bidang Sarpras, Wakil Kepala Sekolah Bidang Siswa, Instruktur/Pembimbing DuDi, dan Peserta didik  yang sudah melaksanakan PSG. Teknik pengambilan data melalui 4 cara yaitu : wawancara, dokumentasi, observasi, dan kuesioner.  Hasil penelitian  pada tahap   1) masukan (antecedents)  meliputi a) pada sistem PPDB menggunakan POS, kriteria kelulusan menggunakan nilai UN dan tes wawancara, belum menggunakan tes akademik, b)   Kurikulum Tingkat Satuan Pendidikan (KTSP),  46 jam per minggu, jam praktek 16 jam; c) administrasi  PSG baik dan lengkap; d) ketersediaan mitra kerja/DuDi mencukupi; belum semua DuDi melaksanakan Mou, e)  kualifikasi guru praktek S.1, belum semua memiliki sertifikat kompetensi, 2) proses (transaction) meliputi a)  pelaksanaan PSG  selama 2 bulan (400 jam), b)  kualifikasi pembimbing PSG S.1, c) kualifikasi instruktur/pembimbing DuDi masih SLTA, d) kriteria penilaian dari pembimbing DuDi mencakup aspek kognitif,  sikap, dan ketrampilan, belum ada  indikator yang  jelas, e) keterlibatan pembimbing DuDi  secara periodik dan sesuai dengan  job pekerjaan, 3)  tahap hasil  (output) meliputi a) nilai hasil belajar/praktek kerja dari aspek kognitif, sikap, dan ketrampilan.  rata-rata minimal 7.5, belum menggunakan indikator yang rinci,  b) nilai hasil  ujian praktek akhir semester  rata-rata minimal 7.5. The declaration of  Central Java Government as a Vocation Province impacts the role of  vocational schools as the centre of  education and  training,  the centre of  science and  technology development, as well as  the centre of  production and marketing. Dual System of Education (DSE) was initiated by the former Ministry of  Education and Culture in 1994 Prof. Dr. Ing Wardiman Djojonegoro. It was a system  that  links and matches  the  interest between education and in-dustry.The objectives of  this research are to examine the implementation level of  Dual System of  Education in phase 1) antecedents consisted of  system/criteria of  student admission, current curriculum, school facilities, DSE administration, industry partnership and teacher qualification; 2) transactions consisted of schedule, supervisor qualification, instructor qualification, assessment criteria, and structural  involvement; 3) output consisted of   student achievement  in  the  form of  assessment  from  the industry,  student achievement after  the  implementation of  Dual System of  Education  in  the final competency test.The subject of the research was the Vice Principle of  Curriculum, the Vice Principle of External Af fair,  the Vice Principle  of  Facility and  Infrastructure, the Vice Principle  of  Student Affair,  Instructor/Supervisor, and students of  Dual System of  Education. The data were gathered  from interview, documentation, observation and questionnaire.The results in phase: 1) antecedents are: a)  in PPDB system using POS,  the criteria  for graduation use national examination score and interview result, not academic  test, b) School Based Curriculu, 46 hours per week, 16 hours for vocational practice, c) well-managed administration, d) sufficient partnership availability, some partners have not  implemented Mou  yet,  e)  bachelor  teacher  qualification, some  teachers  have  not had  competence  certificates; 2) transactions are: a) DSE implementation in 2 months (400 hours), b) DSE supervisor qualification, c) instructor qualifi-cation, d) assessment criteria with cognitive, af fective and skill aspect with unobvious indicator, e) supervisor involvement periodically according to  the  job description; 3) outputs are: a) result of  vocational  study and practice  from cognitive, affective and skill aspect. The mean was 7.5 with undetailed indicator, b) result of  final vocational practice. The mean was 7.5 with unobvious indicator.